Subjective Evaluation of Place Environmental Quality in Conference and Exhibition Buildings in Small- and Medium-Sized Cities: An Empirical Case Study - Yuchen Xie; Jianhe Luo; Peng Du (Buildings)
The environmental quality of conference and exhibition places in small- and medium-sized cities plays a crucial role in attracting exhibitors, fostering the growth of the conference and exhibition industry and enhancing the market competitiveness of these places. However, past decision makers have often adopted planning models from large cities, neglecting the interaction between conference and exhibition places in smaller cities and local lifestyles as well as urban environments. From an “environment-behavior” perspective, this study reveals the unique interaction mechanisms between exhibitors and the built environment within such venues. Moving beyond the limitations of traditional research that focused solely on physical indicators, we place particular emphasis on exhibitors’ behavioral adaptations and their overall exhibition experience in the convention environment. To address this gap, this study employs a mixed-method approach that integrates field surveys, interviews, and questionnaires to systematically collect data from 10 representative cases. First, a preliminary study was conducted to establish an evaluation index system for place environmental quality. Through regression analysis, six key indicators—such as promotional atmosphere, site accessibility, and surrounding urban development conditions—were identified as significant factors influencing place quality. Second, subjective evaluations were conducted based on users’ actual experiences and experts’ professional insights, leading to the development of an importance–performance analysis model to assess value expectations and place environmental performance. The results indicated that users had high expectations for elements such as parking availability, transportation facilities, and the surrounding commercial atmosphere. In contrast, experts emphasized the significance of proximity to urban transportation hubs, site accessibility, and the spatial orientation of public spaces in determining environmental quality. Moreover, differences in evaluations among experts from various fields revealed notable variations in focus and priority considerations. Finally, based on a statistical analysis of the survey results, this study proposes three design recommendations—“adaptation, attraction, and quality enhancement”—to optimize the environmental quality of conference and exhibition places in small- and medium-sized cities, offering both theoretical and practical guidance for future planning, design, and evaluation.